Scientific substantiation of the maximum allowable concentration of the new insecticide spiromesifen in the water of model reservoirs - Tkachenko , Inna; Antonenko , Anna (The Ukrainian Scientific Medical Youth Journal, 2023)
the rational use of pesticides is an important and very complex matter, therefore, the introduction of pollutants into agriculture must consider economic, social and, especially, environmental aspects. The presence of standardization and regulation of chemical plant protection agents in environmental objects (water, plants, soil, air of the working zone and atmospheric air) is a legally necessary condition for the pesticides application. After all, the presence of compounds residual amounts in water and food products can lead to the emergence of various diseases and disorders in the human body. The aim of our research was to standardize the new insecticide spiromesifen in the water of model reservoirs for use in economic, drinking and cultural and household purposes. When substantiating the maximum allowable concentration of the compound, we used generally accepted methodological approaches, laboratory and natural methods of evaluating water according to organoleptic (color, smell, transparency, turbidity, foaming) and general sanitary indices (biochemical oxygen consumption, amount of aquatic microflora, ammonia nitrogen, nitrogen nitrites, nitrogen nitrates, dissolved oxygen level, active reaction of water). The sanitary-toxicological hazard index of spiromesifen was also calculated for the studied water samples. The obtained results of the study on the ability of spiromesifen to affect the organoleptic properties of water (smell in 2 points at 20 and 60 °C), nitrification and ammonification processes allowed to establish a limiting value at the level of 0.002 mg/dm3. According to the content of oxygen dissolved in water and the effect on the active reaction of water (pH) and the value of the maximum inactive concentration (as a sanitary and toxicological index of harmfulness), the value was justified – 0.02 mg/dm3. When studying the dynamics of biochemical oxygen consumption and the growth and development of saprophytic microflora, the influence of spiromesifen in concentrations of 0.02 and 0.002 mg/dm3 was revealed. Accordingly, these specified processes became the limiting criteria when establishing the maximum allowable concentration of spiromesifen in the water of model reservoirs, which was 0.0002 mg/dm3 (according to the general sanitary index).